A brief history of Romanian psychology. Issue 1 (2nd September 2022) - David, Daniel; Ștefan, Simona; Nechita, Diana; Dobrean, Anca
Abstract: The evolution of Romanian psychology followed several stages, similarly to other countries in Eastern Europe, yet with its own particularities. The first psychology institutes were introduced by former students of Wilhelm Wundt, and the field saw a rapid development, with distinguished scholars making relevant scientific contributions. However, after the communist regime was enforced, psychology stagnated somewhat due to ideological, financial, and political reasons, and, in 1977, it was even removed from academia. After 1989, psychology revived in academia and research, and as a profession as well. This article summarizes the evolution of Romanian psychology through these stages, focusing on its postcommunist revival.